Mycobacterium Cytidylate Kinase Appears to Be an Undruggable Target. (August 2016) - Craig, Justin K.; Risler, Jenni K.; Loesch, Kimberly A.; Dong, Wen; Baker, Dwight; Barrett, Lynn K.; Subramanian, Sandhya; Samudrala, Ram; Van Voorhis, Wesley C.
New and improved drugs against tuberculosis are urgently needed as multi-drug-resistant forms of the disease become more prevalent. Mycobacterium tuberculosis cytidylate kinase is an attractive target for screening due to its essentiality and different substrate specificity to the human orthologue. However, we selected the Mycobacterium smegmatis cytidylate kinase for screening because of the availability of high-resolution X-ray crystallographic data defining its structure and the high likelihood of active site structural similarity to the M. tuberculosis orthologue. We report the development and implementation of a high-throughput luciferase-based activity assay and screening of 19, 920 compounds derived from small-molecule libraries and an in silico screen predicting likely inhibitors of the cytidylate kinase enzyme. Hit validation included a counterscreen for luciferase inhibitors that would result in false positives in the initial screen. Results of this counterscreen ruled out all of the putative cytidylate kinase inhibitors identified in the initial screening, leaving no compounds as candidates for drug development. Although a negative result, this study indicates that this important drug target may in fact be undruggable and serve as a warning for future investigations.